Acute ischaemic stroke: recent advances in reperfusion treatment. (7th December 2022) - Widimsky, Petr; Snyder, Kenneth; Sulzenko, Jakub; Hopkins, Leo Nelson; Stetkarova, Ivana
Graphical Abstract: Graphical Abstract Upper part left: angiography of an occluded middle cerebral artery (typical image in an acute anterior circulation stroke). Upper middle: ongoing ischaemia in the brain area, supplied by the occluded artery. Upper right: computed tomography and perfusion computed tomography images in the acute phase of anterior circulation stroke. Lower part left: intravenous thrombolysis is recommended within 4.5 h of symptom onset (if no contraindication is present). Lower middle: endovascular treatment (i.e. thrombectomy with stent retriever and/or aspiration catheter) is recommended within 6 h of symptom onset, irrespective of whether intravenous thrombolysis was given or not. Lower right: Time window for endovascular treatment may be extended up to 24 h from symptom onset when significant penumbra is proven by advanced imaging methods (e.g. perfusion computed tomography). ASPECT, Alberta Stroke Programme Early CT; CT, computed tomography; DSA, digital subtraction angiography; EVT, endovascular treatment; IVT, intravenous thrombolysis; LVO, large-vessel occlusion; NIHSS, National Institutes of Health Stroke Scale. Abstract: During the last 5–7 years, tremendous progress was achieved in the reperfusion treatment of acute ischaemic stroke during its first few hours from symptom onset. This review summarizes the latest evidence from randomized clinical trials and prospective registries with a focus on endovascular treatment using stent retrievers, aspiration catheters, thrombolytics, and (in selected patients) carotid stenting. Novel approaches in prehospital (mobile interventional stroke teams) and early hospital (direct transfer to angiography) management are described, and future perspectives ('all-in-one' laboratories with angiography and computed tomography integrated) are discussed. There is reasonable chance for patients with moderate-to-severe acute ischaemic stroke to survive without permanent sequelae when the large-vessel occlusion is removed by means of modern pharmaco-mechanic approach. Catheter thrombectomy is now the golden standard of acute stroke treatment. The role of cardiologists in stroke is expanding from diagnostic help (to reveal the cause of stroke) to acute therapy in those regions where such up-to-date Class I. A treatment is not yet available.